Orquídeas de Bolivia y Perú, Novedades Taxonómicas I (Pleurothallidinae) - Jiménez Pérez, Iván (Lankesteriana: International Journal on Orchidology, 2015)
Seven new orchids species belonging to the subtribe Pleurothallidinae from the montane forest of the eastern Andean slopes, six of them from Bolivia and one from Bolivia and Peru, are described and illustrated: Brachionidium lopez-robertsiae, Brachionidium sulcatum, Lepanthopsis trulliformis, Stelis pertusa, Trichosalpinx adnata, Trichosalpinx gabi-villegasiae and Trichosalpinx giovi-mendietae. Information on habitat, distribution and phenology is provided for each species. Also critical characters and affinities with similar species are commented.